Effect Of Credit Risk Management On Financial Performance Of Commercial Banks Listed In The Malaysia Stock Exchange - Haneem Binti Muhamad Anuar
Banks are the most prominent players in the financial market. The ups and downs of banks may signal the growth of a country's economy. Unlike firms, banks are also known as 'too big to fail' entities since their bankruptcy may stir the country's economy. Due to that, risk-averse investors may opt to invest in banks for safe income generation. One of the methods to observe the bank's performance is by viewing the bank's stock price trend. A consistent, low fluctuation or increasing pattern of the bank's stock price indicates the bank is performing well. This study investigates the relation of a bank's price performance with the credit risk practice. This study argues that good credit risk practice in banks may influence their stock price performance. The argument is supported by the theoretical profound that credit creation is banks' main activity. Hence, managing credit risk exposure may contribute to better bank sustainability and better price performance. This study uses four variables—Loan Loss Provision (LLP), Loan Loss Reserve (LLR), Non-performing loan (NPL) and Net Charge Off ratio (NCR) to indicate the credit risk practice of ten commercial banks listed in the Malaysian Stock Exchange. Using the Panel Data Analysis method, the results show LLR and NPL have a significant positive relationship to the bank's performance. In contrast, LLP and NCR have a negative significance relationship. While the LLP and NPL results contradict the theory, individual investigation on the variables has identified the need to deepen the study on these variables in the future to determine their relation to the bank's performance. The analysis of these four variables is unique compared to the other studies since it uses different variables to measure the bank's credit risk than in Basel II. Hence, this study contributes to the credit risk research field by investigating more variables to indicate banks' credit risk exposure. The findings are beneficial for investors to predict their investment portfolio and for the banks to remain resilient against any financial circumstances.